2004
DOI: 10.2466/pr0.94.3.785-792
|View full text |Cite
|
Sign up to set email alerts
|

Telephone-Based Treatment for Family Practice Patients with Mild Depression

Abstract: The need for treating milder forms of depression has recently been of increased interest. This was a randomized, controlled study to evaluate the effects of telephone-based problem-solving therapy for mild depression. Comparison groups were a treatment-as-usual group and another group receiving stress-management training by telephone. From 1,742 family practice patients screened for depression, 54 with mild depression entered the study. Treatment was provided by experienced family practice nurses, trained and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 10 publications
0
19
0
4
Order By: Relevance
“…[29][30][31] Six of 8 studies that used telephone-based approaches showed TMH to be successful, but with a need for follow-up study. [32][33][34][35][36][37][38] One study indicated TMH was unsuccessful, 39 and results from another were unclear. 40 A high-quality RCT found that treatment of depression by telepsychiatry and face-to-face intervention had comparable outcomes.…”
Section: General Psychiatric and Mental Health Servicesmentioning
confidence: 99%
“…[29][30][31] Six of 8 studies that used telephone-based approaches showed TMH to be successful, but with a need for follow-up study. [32][33][34][35][36][37][38] One study indicated TMH was unsuccessful, 39 and results from another were unclear. 40 A high-quality RCT found that treatment of depression by telepsychiatry and face-to-face intervention had comparable outcomes.…”
Section: General Psychiatric and Mental Health Servicesmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][34][35][36][37][38][39][40][41] In these 15 studies, a total of 1505 patients participated (804 in the psychological treatment conditions and 701 in the control conditions). Selected characteristics of the studies included are presented in Table 1.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Interventionen, Zielgruppen und Rahmenbedingungen Bisher evaluierte TPT-Programme bei Depression sind meist kognitiv-verhaltenstherapeutisch orientierte Kurzzeitinterventionen mit etwa 6-18 telefonischen Sitzungen von 30-bis 50-minüti-ger Dauer [Lynch et al, 2004;Mohr et al, 2011Mohr et al, , 2012Simon et al, 2004;Tutty et al, 2010]; auch interpersonelle TPT wurde untersucht [Miller und Weissmann, 2002]. Die TPT-Programme beziehen sich in der Regel auf zentrale Elemente der verhaltenstherapeutischen Depressionsbehandlung, d.h. auf Psychoedukation, behaviorale Aktivierung und kognitive Umstrukturierung [Mohr et al, 2012;Simon et al, 2004].…”
Section: Bisherige Tpt-programme Bei Depressionunclassified
“…Die Zielgruppe bisher untersuchter TPT-Angebote für Depression sind meist Patienten, die im Vorfeld ein primärärztliches Setting aufsuchen [Lynch et al, 2004;Mohr et al, 2011;Simon et al, 2004;Tutty et al, 2010], oder Angestellte, die TPT als betriebliches Gesundheitsangebot nutzen [Bee et al, 2010a]. Verschiedene Programme richten sich an Patienten mit unterschiedlich schwerer Depression: Während an einigen Angeboten Patienten mit jeglicher Depressionsymptomatik teilnehmen können [Bee et al, 2010a;Simon et al, 2004;Tutty et al, 2010], schließen andere nur Patienten mit der Diagnose einer Major Depression [Mohr et al, 2011[Mohr et al, , 2012 und weitere nur solche mit subklinischer oder leichtgradiger Depression [Lynch et al, 2004] ein.…”
Section: Bisherige Tpt-programme Bei Depressionunclassified
See 1 more Smart Citation